PERBEDAAN PENGGUNAAN METODE PEMBELAJARAN DRILL DAN PEER TEACHING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN AKUNTANSI DASAR SMKN 22 JAKARTA - Nasywa Dzakirah; Santi Susanti; Wahyu Lestari (Qalam : Jurnal Ilmu Kependidikan, 2026)
This study aims to analyze the differences in learning outcomes between students taught using the Drill learning method and those taught using the Peer Teaching learning method in the Basic Accounting subject on the Accounting Cycle of Trading Companies at Vocational High School 22 Jakarta. This study employed a quantitative approach using a quasi-experimental method with a Posttest-Only Nonequivalent Control Group Design. The unit of analysis consisted of 72 tenth-grade students in the Banking Services program at SMK Negeri 22 Jakarta. A saturated sampling technique was employed, in which the entire population was selected as the research sample, consisting of 36 students in the control class and 36 students in the experimental class. Data were collected through a practical test designed to assess students' cognitive and psychomotor learning outcomes. The data were analyzed using descriptive and inferential statistics, including the Shapiro–Wilk normality test, Levene's Test for Homogeneity of Variance, and the Independent Samples t-test, using IBM SPSS Statistics. The findings revealed that the mean learning outcome of students in the control class taught using the Drill method was 81.25, while the mean score of students in the experimental class taught using the Peer Teaching method was 88.39. The hypothesis test yielded a significance value (Sig. (2-tailed)) of 0.049, which was lower than 0.05, indicating a statistically significant difference in learning outcomes between students taught using the Drill method and those taught using the Peer Teaching method. Therefore, the Peer Teaching method may be considered an alternative instructional approach for teaching Basic Accounting, particularly the Accounting Cycle of Trading Companies, while taking into account the characteristics of the learning material and students' needs. Keywords: Drill, Peer teaching, Learning outcomes, Basic accounting, Accounting cycle of trading companies